2013
DOI: 10.1186/1756-9966-32-21
|View full text |Cite
|
Sign up to set email alerts
|

Decrease expression of microRNA-20a promotes cancer cell proliferation and predicts poor survival of hepatocellular carcinoma

Abstract: BackgroundGrowing evidences indicate microRNAs play important roles in cancer development, progression, metastasis and may constitute robust biomarkers for cancer prognosis. The aim of this study was to identify the clinical and functional association of microRNA-20a (miR-20a) in hepatocellular carcinoma (HCC).MethodsMiR-20a was detected using Taqman real-time polymerase chain reaction. Kaplan-Meier and Cox proportional regression analyses were utilized to determine the association of miR-20a with survival of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 29 publications
1
72
0
Order By: Relevance
“…Studies have shown that miR-20a exhibits different expression profiles in different types of cancer (11)(12)(13)(15)(16)(17)(18). Upregulation of miR-20a has been found in GBC (13), colon adenocarcinoma (15) and gliomas (16), while miR-20a down- regulation has been reported in primary HCC (11), OSCC (12), breast cancer (17) and pancreatic carcinoma (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that miR-20a exhibits different expression profiles in different types of cancer (11)(12)(13)(15)(16)(17)(18). Upregulation of miR-20a has been found in GBC (13), colon adenocarcinoma (15) and gliomas (16), while miR-20a down- regulation has been reported in primary HCC (11), OSCC (12), breast cancer (17) and pancreatic carcinoma (18).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of miR-20a has been found in GBC (13), colon adenocarcinoma (15) and gliomas (16), while miR-20a down- regulation has been reported in primary HCC (11), OSCC (12), breast cancer (17) and pancreatic carcinoma (18). This suggests that the function of miR-20a may vary among different types of tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-106a was previously shown to be downregulated in glioma, colon cancer, squamous cell carcinoma and astrocytoma, and functions as a tumor suppressor by targeting solute carrier family 2 (facilitated glucose transporter), member 3 (33), E2F transcription factor 1 (34) and Fas-activated serine/threonine kinase (35). Similarly, miR-20a is downregulated in hepatocellular carcinoma (HCC) and correlated with HCC recurrence and poor prognosis (36). In addition, miR-425 is able to reduce proliferation, impair tumorigenesis and metastasis, and increase expression of epithelial markers in aggressive breast cancer cells by targeting SATB homeobox 1, CCND2 and Fascin actin-bundling protein 1 (37).…”
Section: Discussionmentioning
confidence: 99%
“…The survival of HCC patients after resection remains poor, mainly attributing to frequent metastases and recurrence [2]. Recently, plenty of researches have performed to explore mechanisms underlying the initiation, propagation and development of HCC [3,4]. However, the complexity of HCC need further hypothesis-drove researches to be exerted.…”
Section: Introductionmentioning
confidence: 99%